Impact of Nuts Consumption On Antioxidant Status and Pro-Oxidant Parameters in Healthy Human Volunteers - Al-Habib, Omar A.M.; AL-Kass, Suad Y.; Jasim, Kajeen H. (Science Journal of University of Zakho, 2016)
The aim of the current research was to study the effect of consumption of a mixture of almond and pistachio on antioxidants and pro-oxidants levels in healthy human volunteers.  This dietary intervention study was carried out during the period from February to March, 2013 on a total of 48 apparently healthy males students from Military Academy / Zakho, Kurdistan Region- Iraq. Blood samples were withdrawn from all volunteer who were living in a controlled environment and analyzed for the determination of serum antioxidants, pro-oxidants. Parameters were obtained at baseline, 3 and 6 weeks after daily consumption of 50 gm. of a mixture of almond and pistachio.The results of the current study demonstrated that daily consumption of 50 g of   almond and pistachio mixture for 3-6 weeks, significantly increased (P
Keywords: Anti-oxidants; Pro-oxidants; Human volunteers; Almond; Pistachio